A brief analysis of language tasks used by air traffic controllers in radiotelephony communications in Brazil - Aragão, Beatriz Faria; Scaramucci, Matilde Virginia Ricardi (The ESPecialist, 2020)
This article reports the results of a study, conducted by the EPLIS (the SISCEAB Aeronautical English Language Proficiency Exam) development team, which consisted, among other things, of an analysis followed by discussion of the language tasks listed in Appendix B of the Manual on the Implementation of Language Proficiency Requirements (Doc 9835, ICAO, 2010). Although those language tasks supposedly represented language used by air traffic controllers, they were considered too vague to be used to improve the exam or to develop teaching and assessment materials. The study was carried out by a team of five experienced and proficient air traffic controllers from different facilities and a language expert with experience in teaching and assessing English for specific purposes using a focus group methodology. The results have shown that the most frequently used language tasks are related to traffic management, mostly covered by phraseology. On the other hand, language tasks involving explanation and clarifications, which are highly recurrent in radiotelephony communications, require the use of plain language. Additionally, the analysis has revealed that although some language tasks might not be so complex in terms of language, nor so frequently used, they play an important role in the safety of operation.